Immune accompaniment of quantitative-qualitative blood pressure clusters in patients of Truskavets’ spa - Kozyavkina, Nataliya; Vovchyna, Yuliya; Voronych-Semchenko, Nataliya; Zukow, Walery; Popovych, Dariya; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. Earlier we studied the neural, endocrine, and metabolic accompaniments of quantitative-qualitative blood pressure (BP) clusters of profile patients of Truskavets’ spa. The purpose of this study is to clarify the immune accompaniment in the same contingent. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP. We determined in the blood the relative content of leukocyte forms, of T-lymphocytes and their killer, helper and regulatory subpopulations as well as NK- and B-lymphocytes; in serum - the concentration of C-reactive protein, Tumor Necrosis Factor-α, Interleukins 1β and 6, immunoglobulins classes G, A, and M as well as circulating immune complexes; in saliva - IgG, IgA, and secretory IgA. In addition, we determined parameters of phagocytosis by neutrophils of Staph. aureus and E. coli; components of stool and urine microbiota. Results. The forward stepwise program identified 18 parameters as characteristic of quantitative-qualitative blood pressure clusters. In addition to BP parameters by default, the most informative among them are serum levels of IL-6 and TNF-α as well as activity and intensity of phagocytosis by neutrophils of Staph. aureus. The accuracy of patient classification is 96,6%. Conclusion. The quantitative-qualitative blood pressure clusters have a characteristic immune accompaniment.